Befriending breastfeeding: a home-based antenatal pilot for South Asian families. - Douglas, Naomi (Community Practitioner, 2012)
In the last decade recognition of the impact of social inequalities on health has resulted in a refocus of the public health agenda, with health visitors having a pivotal role. While this involvement is in the form of family-centred public health, it is also intended to involve work with the wider community and primarily focuses on beginning to address the injustice of inequality before a child is born, acknowledging that early intervention is key to breaking the cycle of deprivation. Such inequalities disproportionately affect those from black and minority ethnic (BME) groups who are more likely to report long-term ill health than their white counterparts. Access to healthcare services is restricted not only by family choices but also by difficulties of location and language. Numerous initiatives to address these issues have been implemented in the last 10 years, from Sure Start centres to maternity service reform, but the level of engagement from women from BME groups is not equal to their counterparts. In the locality of Iffley/Cowley in Oxford, there is a high concentration of families from Pakistan and Bangladesh who, despite concerted efforts, have remained hard to reach. This project attempted to redesign the current antenatal breastfeeding information service, and aimed to produce evidence to guide practice to better connect with this group. The review considers evidence provided by the literature base and uses a home visiting approach to investigate the topic. Results are correlated and compared, and recommendations for the future are presented.